2013
DOI: 10.12816/0006037
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge , Attitude and Practices among Gynecologists regarding Oral Health of Expectant Mothers of Vadodara City , Gujarat

Abstract: A Ab bs st tr ra ac ct t: :Background and Objectives: To assess the knowledge, attitude and practices among Gynecologists' regarding oral health of expectant mothers of Vadodara city, by using self designed, structured, pre-tested close ended questionnaire. Methodology:Total of 130 gynaecologists are included in the study. Ethical approval was obtained by the Ethics committee, Sumandeep Vidyapeeth, Vadodara. Prior to study, questionnaire was pre-tested and validated. Those individuals who participated in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(8 reference statements)
2
3
0
Order By: Relevance
“…This is different from the results of studies by Cohen 28 and Patil et al, 11 which indicated the awareness of 74.7% and 32.98% of participants, respectively, about the effects of women's hormonal changes on gingival health. This study also showed no statistically significant relationships between the age or the occupational experience of the participants and their level of knowledge, consistent with the results reported by Shah et al, 29 who emphasized the absence of a statistically significant relationship between age and awareness of participants. On the other side, these results are different from the results reported by Cohen et al, 28 who reported that the awareness of gynecologists about periodontal diseases increased proportional to their work experience.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is different from the results of studies by Cohen 28 and Patil et al, 11 which indicated the awareness of 74.7% and 32.98% of participants, respectively, about the effects of women's hormonal changes on gingival health. This study also showed no statistically significant relationships between the age or the occupational experience of the participants and their level of knowledge, consistent with the results reported by Shah et al, 29 who emphasized the absence of a statistically significant relationship between age and awareness of participants. On the other side, these results are different from the results reported by Cohen et al, 28 who reported that the awareness of gynecologists about periodontal diseases increased proportional to their work experience.…”
Section: Discussionsupporting
confidence: 92%
“…On the other side, these results are different from the results reported by Cohen et al, 28 who reported that the awareness of gynecologists about periodontal diseases increased proportional to their work experience. 82.5% of the participants of the present study considered premature delivery and 75% of them considered low birth weight as the consequences of maternal periodontal disease, which is consistent with the results of studies by Patil et al, Shah et al, Suri, Cohen, Hashim and Laslowski, in which most of the participants considered periodontal disease as a risk factor for adverse outcomes of pregnancy, including low birth weight or premature delivery, 11,[28][29][30][31][32][33] while in the study by Shenay, 26 fewer participants considered periodontal disease as a risk factor for inappropriate pregnancy complications despite their proper knowledge about oral manifestations of periodontal diseases. In a study by Bahalla, 34 the participants only considered vaginal infection as a cause of low birth weight or premature delivery and only reported infectious endocarditis as the main consequence of periodontal disease.…”
Section: Discussionsupporting
confidence: 90%
“…Obstetrician-gynecologists are in an ideal position to improve the oral health of mothers and to avoid any problems during pregnancy, as they often see pregnant women or women who are about to become pregnant. Various studies have been conducted to measure the knowledge and attitudes of obstetrician-gynecologists regarding the relationship between periodontal disease and pregnancy in different countries, including the USA, Brazil, France, India, Iran, the United Arab Emirates and Saudi Arabia ( 46 , 47 , 48 , 49 , 50 , 52 , 56 , 57 , 58 , 59 ). The aim of this study was to investigate the level of this knowledge and attitudes towards this relationship among Turkish experts.…”
Section: Discussionmentioning
confidence: 99%
“…14 Our study results were also similar with Shah et al who noted insignificant relationship between gynecologists knowledge and their ages. 15 During pregnancy about the oral and dental hygiene measures > 80% participants assumed that scaling and plaque control decrease the "gingivitis" and 75% respondents believed that pregnancy can cause bleeding and gingivitis. Our these finding are in line with results of Shenoy's et al who found it to be 77%.…”
Section: Resultsmentioning
confidence: 99%